Pemberantasan Korupsi dalam Reformasi Birokrasi di Vietnam - Alim Bathoro (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2016)
This research discusses the reformation of bureaucracy in Vietnam. The elites of the central government were involved in the process. This study questions state-elite relations in implementing reformation of bureaucracy in combating corruption, what form, what factors shape the form and under what circumstances does it change. Studies on this subject varies from statist, elitist approach. The statist approach focuses on the role of the state, questioning whether it dominate the politics (Evans),. Elitist approach focuses on the concentration and exercise of power by elites (Mills, Mosca, Pareto, and Keller) in shaping policies. This research shows that the conflict between the central elite is caused by dispute over implementing reformation of bureaucracy in combating corruption. The dispute over implementing reformation of bureaucracy within the administration had led to the function of state autonomy in which case is combating corruption indicated by how the state not seriously became government program. This occurred due to the ability of the international issue to influence the policy of Vietnam government. In turn this impacted the state, in this case the government of Vietnam, to be capable of taking normal political decisions but to be incapable taking political decisions of combating corruption. This study supports and corroborates state autonomy theory on the state as dominate policies of combating corruption. In particular on state autonomy that is shown by the interest of elites of central government. In theory of the state’s autonomy is the manner in which the state manages the distortion or pressure of the global issue of corruption.